SOME METHODS OF THE DECISION OF PROBLEMS OF NUCLEAR PHYSICS ON THE CONNECTED CONDITIONS - Dubovichenko, S.B. (Recent Contributions to Physics, 2008)
Some not standard methods for numerical decided of the Schrodinger equation or system of the Schrodinger equation with tensor force in nuclear physics tasks at low energies and nuclear astrophysics was consider. These methods are applicable for analysis of the bound states of atomic nucleus in potential cluster models.